The Zeroth of Generation Zh of Fermion, A Unified Mass Theory of Twelve Elementary Fermions (Global Journal of Science Frontier Research, 2026)
Abstract- This paper postulates: The existence of The Zeroth of Generation Zh of Fermion. Zh comprises four Zero-Mass particles (Ψ(0) = (α(0), β(0), γ(0), δ(0))). Particle Ψ(0) could offer the guidance to accomplish a unified mass theory of twelve elementary fermions in particle physics.
Keywords: The Zeroth Generation Zth; Zero-Mass particle (α(0), β(0), γ(0), δ(0)); Non-Zero-Mass particle (Dirac Particle); Mass Principle; Identical Particle; Pauli Exclusion Principle; Colorized Quantum Number; Function-Q(ω, ξ); Function-ξ(ω); Table 0; ScalarProduct-Mass Equation; Charge-Transition